Retrograde Transport from the Pre-Golgi Intermediate Compartment and the Golgi Complex Is Affected by the Vacuolar H(+)-ATPase Inhibitor Bafilomycin A1 - Palokangas, Harri (The American Society for Cell Biology, 1998)
The effect of the vacuolar H(+)-ATPase inhibitor bafilomycin A1 (Baf A1) on the localization of pre-Golgi intermediate compartment (IC) and Golgi marker proteins was used to study the role of acidification in the function of early secretory compartments. Baf A1 inhibited both brefeldin A- and nocodazole-induced retrograde transport of Golgi proteins to the endoplasmic reticulum (ER), whereas anterograde ER-to-Golgi transport remained largely unaffected. Furthermore, p58/ERGIC-53, which normally cycles between the ER, IC, and cis-Golgi, was arrested in pre-Golgi tubules and vacuoles, and the number of p58-positive ∼80-nm Golgi (coatomer protein I) vesicles was reduced, suggesting that the drug inhibits the retrieval of the protein from post-ER compartments. In parallel, redistribution of β-coatomer protein from the Golgi to peripheral pre-Golgi structures took place. The small GTPase rab1p was detected in short pre-Golgi tubules in control cells and was efficiently recruited to the tubules accumulating in the presence of Baf A1. In contrast, these tubules showed no enrichment of newly synthesized, anterogradely transported proteins, indicating that they participate in retrograde transport. These results suggest that the pre-Golgi structures contain an active H(+)-ATPase that regulates retrograde transport at the ER–Golgi boundary. Interestingly, although Baf A1 had distinct effects on peripheral pre-Golgi structures, only more central, p58-containing elements accumulated detectable amounts of 3-(2,4-dinitroanilino)-3′-amino-N-methyldipropylamine (DAMP), a marker for acidic compartments, raising the possibility that the lumenal pH of the pre-Golgi structures gradually changes in parallel with their translocation to the Golgi region.